ANALISIS PENGARUH PINJAMAN LUAR NEGERI, SURAT UTANG NEGARA, PENERIMAAN PAJAK DAN INFLASI TERHADAP DEFISIT ANGGARAN DI INDONESIA SEBELUM DAN SESUDAH TAHUN 2000 - Agustina Suryani; Anthony Mayes; Rosyetti ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to examine the effect of variable foreign debt, tax revenues and inflation of budget deficit in Indonesia in the year of 1985-1999; and the effect of variable foreign debt, government debt securities, tax revenue and inflation of budget deficit in Indonesia in the year of 2000-2015. This research used secondary data in the year of 1985-2015 sourced from Nota Keuangan and Statistik Ekonomi dan Keuangan Indonesia. In this research use analysis method with multiple linear regression analysis before and after 2000, using analysis tool SPSS version 23. Based on the results of these tests show that in the year of 1985-1999 variable foreign debt, tax revenue and inflation simultaneously significantly to influential of Indonesia’s budget deficit with F-statistic 96,550 with probabilty value is 0,000 and value is 0,953 containing the meaning of 95,3 percent budget deficit influenced by foreign debt, tax revenues and inflation. And in the year of 2000-2015 variable government debt securities, foreign debt, tax revenue and inflation simultaneously significantly to influential of Indonesia’s budget deficit with F-statistic 30,394 with probabilty value is 0,000 and value is 0,887 containing the meaning of 88,7 percent budget deficit influenced by government debt securities, foreign debt, tax revenues and inflation.Keyword : Budget Deficit, Foreign Debt, Government Debt Securities, Tax Revenue And Inflation.